Season and breed effect in fresh semen parameters at a bull semen production center in Peru - Dipaz Berrocal, Deysi (2024)
In the present study, the effect of breed, season, and their interaction on semen volume, sperm concentration, and motility was tested. Nine bulls were tested: three Braunvieh, three Simmental (B. taurus), and three Gyr (B. indicus). These bulls were managed equally in a cold semi-arid climate, divided into hot (from November to April) and cold (from May to October) for maximum and minimum temperature and relative humidity. Semen was collected twice a week for 24 consecutive months. MANOVA by ranks was used to determine significant effects; breed had a significant effect (P<0.001) on semen parameters, and seasonal variations were not significant (P>0.05). However, there was a significant effect (P<0.001) for the interaction between breed and season. To evaluate differences between breeds, we performed Tukey's post-hoc test; all pairwise comparisons (Braunvieh-Gyr, Braunvieh-Simmental and Gyr-Simmental) showed significant differences (P<0.001). Nonparametric one-way analysis showed significantly higher B. taurus breeds’ sperm concentration and B. indicus breed’s semen volume. For interaction between breed and season, Gyr reported higher sperm volume than B. taurus breeds in both seasons (P>0.05), but B. taurus breeds had higher sperm concentration in the cold season. The findings will help management make better decisions in semen collection, especially during peak season.